Hibridación interespecífica de arroz (Oryza sativa L. ssp. indica x Oryza sp.) para la obtención de segregantes F1 - Toala Pita, Dayse Magaly (2025)
Rice cultivation (Oryza sativa L.) It is one of the fundamental pillars of global food security, being a primary source of much of the population, as global demand increases, putting pressure on farmers to develop rice varieties more resistant to pests and diseases. This interspecific hybridization project of rice (Oryza sativa L.) was carried out with the aim of obtaining F1 segregants. It was held in the CEDEGE area, Babahoyo canton, Los Ríos province. The growth blocks of the parents were carried out at the El Palmar Experimental Farm, and the crosses were carried out on the premises of the Faculty of Agricultural Sciences of the Technical University of Babahoyo. A population of 12 reciprocal crosses was obtained, crossing 1 female parent x 6 male parents; and at the same time 6 female parents x 1 male parent. 1. SFL11 (male parent) x L-07, L-17, L-27, L-37, L-38 and GR (female parents); and, 2. L-07, L-17, L-27, L-37, L-38 and GR (Male Parents) x SFL11 (Female Parent). The variables recorded were the following: Number of emasculated (pollinated) flowers, Number of seeds harvested, Percentage of seeds harvested, Length (mm) and width (mm) of the seeds harvested. In this research, two tests were used, the Tukey Test and the "t-test" for paired samples, which allowed comparing the means of an experimental variable. As for the results, the crosses of genetic progenitors produce a wide genetic diversity, that for every 100 emasculated flowers a total of 30 seeds formed were achieved, which allows the timely selection of F1 segregants. There is genetic compatibility between the improved genotypes and SFL-11 commercial rice due to the fact that F1 seeds were obtained by simple hybridization